Maternal risk factors for neonatal jaundice: a hospital-based cross-sectional study in Tehran - Reza Tavakolizadeh; Anahita Izadi; Golnar Seirafi; Leila Khedmat; Sayed Yousef Mojtahedi (European Journal of Translational Myology, 2018)
Diagnosis and timely treatment of neonatal jaundice is critical to preventing its dangerous side effects. Knowing the predisposing factors of neonatal jaundice is still a serious debate, which can be effective in controlling jaundice and the primary problem. The aim of this study was to evaluate maternal risk factors that contribute to the Hyperbilirubinemia among newborns admitted to Imam Khomeini and Ziaeean hospitals during 2015. We collected random samplings for the current study. Medical records for all newborns with jaundice were examined for risk factors associated with Hyperbilirubinemia. All variables were analyzed by SPSS software, version 19. Chi-square test and T-test were applied to evaluate qualitative and quantitative data, respectively. Our findings revealed that maternal age, weight, BMI, WBC, Hb, PLT, birth in the first pregnancy, numbers of pregnancies and prolonged delivery were significantly associated with bilirubin levels. Preventing the risk correlated with maternal factors or identifying neonates with these risk factors is important in effective management of infants. Therefore, the evaluation of neonatal jaundice in health care services should always be considered as a fundamental policy.